Personalization and hedonic motivation in creating customer experiences and loyalty in omnichannel retail. (November 2020) - Tyrväinen, Olli; Karjaluoto, Heikki; Saarijärvi, Hannu
Abstract: This study examines the effects of personalization and hedonic motivation on customer experience and its loyalty outcomes in omnichannel retail context. The study develops eight hypotheses which are tested using two survey samples (Finland (n = 2084) and Sweden (n = 2334). In addition, empirical analysis includes 20 semi-structured interviews. The findings support all the hypotheses confirming the positive relationships personalization and hedonic motivation have on cognitive and emotional customer experience components. Further, the positive effects of customer experience on loyalty are confirmed. The results provide both theoretical and managerial insights for improved CX and customer loyalty.